Decrease in p3‐Alcβ37 and p3‐Alcβ40, products of Alcadein β generated by γ‐secretase cleavages, in aged monkeys and patients with Alzheimer's disease. Issue 1 (1st January 2019) - Hata, Saori; Omori, Chiori; Kimura, Ayano; Saito, Haruka; Kimura, Nobuyuki; Gupta, Veer; Pedrini, Steve; Hone, Eugene; Chatterjee, Pratishtha; Taddei, Kevin; Kasuga, Kensaku; Ikeuchi, Takeshi; et al.
Abstract: Introduction: Neuronal p3‐Alcβ peptides are generated from the precursor protein Alcadein β (Alcβ) through cleavage by α‐ and γ‐secretases of the amyloid β (Aβ) protein precursor (APP). To reveal whether p3‐Alcβ is involved in Alzheimer's disease (AD) contributes for the development of novel therapy and/or drug targets. Methods: We developed new sandwich enzyme‐linked immunosorbent assay (sELISA) systems to quantitate levels of p3‐Alcβ in the cerebrospinal fluid (CSF). Results: In monkeys, CSF p3‐Alcβ decreases with age, and the aging is also accompanied by decreased brain expression of Alcβ. In humans, CSF p3‐Alcβ levels decrease to a greater extent in those with AD than in age‐matched controls. Subjects carrying presenilin gene mutations show a significantly lower CSF p3‐Alcβ level. A cell study with an inverse modulator of γ‐secretase remarkably reduces the generation of p3‐Alcβ37 while increasing the production of Aβ42. Discussion: Aging decreases the generation of p3‐Alcβ, and further significant decrease of p3‐Alcβ caused by aberrant γ‐secretase activity may accelerate pathogenesis in AD.